Nanotechnology for environmental sustainability - Mishra, Ajay Kumar (RSYN Proceedings, 2025)
Environmental pollution more specially the water pollution became a major problem today due to contamination discharge by industrial waste. Industrial effluent is the main wastewater pollutants due to their ability to persist in the environment. Variety of materials and techniques are being investigated for the treatment of effluents in wastewater. Green nanocomposites are one of the materials gaining attention due to its excellent physical, chemical, and mechanical properties. Green nanocomposites always act as eco-friendly materials and most favourable materials in current research. The current talk will provide an overview of the current state of nanotechnology-based devices with applications in environmental science, focusing on nanomaterials and polymer nanocomposites. The talk will also pay special attention to those nanotechnology-based approaches that promise easier, faster, and cheaper processes in environmental monitoring and remediation. The talk will highlight the research efforts to enhance the role of the nanocomposite materials in synthetic and wastewater treatment.